A multi-center analysis of the impact of DA-EPOCH-R dose-adjustment on clinical outcomes of patients with double/triple-hit lymphoma. Issue 1 (2nd January 2023) - Cortese, Matthew J.; Wei, Wei; Cerdeña, Sebastian; Watkins, Marcus P.; Olson, Marissa; Jodon, Gray; Kaiser, Jeff; Haverkos, Bradley; Hughes, Mitchell E.; Namoglu, Esin; Grover, Natalie S.; Snow, Anson; et al.
Abstract: Patients with double- and triple-hit lymphomas (DHL/THL) have inferior outcomes with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP), and higher-intensity regimens such as dose-adjusted (DA)-EPOCH-R are standard. Dose-intensification of DA-EPOCH-R is guided by hematologic toxicity, without conclusive benefit for DHL/THL patients. To determine if cumulative doses of DA-EPOCH-R or compliance with dose adjustment impacts survival, we retrospectively evaluated detailed clinical data from 109 adult (age ≥18 years) patients with DHL/THL treated with ≥4 cycles of induction DA-EPOCH-R from 2014 to 2019 at six centers. A comprehensive multivariate analysis was performed. Survival outcomes for the entire cohort were comparable to historical estimates for DHL/THL treated with this regimen (median follow-up 27.9 months). Overall survival (OS) and progression-free survival (PFS) were not significantly associated with cumulative chemotherapy dose, dose escalation, or compliance with dose adjustment. Heterogeneous dosing practices were observed. Prospective investigation is warranted to evaluate the practice of dose adjustment of R-EPOCH for patients with DHL/THL.